The Personhood of Women and Community Development in a Burkinabé Village - Rohatynskyj, Marta (Anthropologica, 2022)
A community actualized development program aiming to assure women equal access to the benefits of development is examined in terms of impact on women’s status. The interaction of the forms of organization envisaged in the village as leading to development and the indigenous structures often lead to conflict. This conflict can be seen as due to the lack of fit between extant forms of organization and those introduced by the development agency. However, it is shown that decisions in contradiction of the desired forms of social action are due to pragmatic choices on the part of the community in relation to realistic goals. It is concluded that such a form of development intervention does not assure equal access of women to the benefits of development.